Pyoverdine-Dependent Virulence of Pseudomonas aeruginosa Isolates From Cystic Fibrosis Patients - Kang, Donghoon; Revtovich, Alexey V.; Chen, Qingquan; Shah, Kush N.; Cannon, Carolyn L.; Kirienko, Natalia V. (Frontiers in Microbiology, 2019)
The development of therapies that modulate or prevent pathogen virulence may be a key strategy for circumventing antimicrobial resistance. Toward that end, we examined the production of pyoverdine, a key virulence determinant, in 70 Pseudomonas aeruginosa isolates from pediatric cystic fibrosis patients. Pyoverdine production was heterogeneous and showed a clear correlation with pathogenicity in Caenorhabditis elegans and an acute murine pneumonia model. Examination showed pyoverdine accumulation in host tissues, including extrapharyngeal tissues of C. elegans and lung tissues of mice, where accumulation correlated with host death. Many of the isolates tested were resistant to multiple antimicrobials, so we assayed the ability of pyoverdine inhibitors to mitigate virulence and rescue pyoverdine-mediated host pathology. Three different classes of pyoverdine inhibitors (gallium, fluoropyrimidines, and LK11) significantly improved survival. Our findings highlight the utility of targeting virulence factors in general, and pyoverdine in particular, as a promising method to control bacterial pathogenesis as the utility of antimicrobials continues to diminish.